Sociology of Terrorism: A Key to Understanding Social Origins? - (:unkn) unknown (ULUSLARARASI ILISKILER KONSEYI DERNEGI, 2010)
Organized violence and terrorist attacks with global connections and transnational implications not only contribute to the deterioration of regional and international relations but also tend to locate and confine international relations analysis to the axis of securitization. Much of the studies on collective violence and terrorism focus on security aspects of such acts but fail to address social roots of conflicts adequately. This article seeks to draw attention to the significance of sociological analysis of acts of terrorism in light of recent scholarship. It argues that without a thorough analysis of social contexts of such acts, fighting terrorism and violence will not be effective and international relations will deteriorate further. Therefore the article concludes that a 'sociology of terrorism' based on interdisciplinary method and approach will complement international relations theory and provide rational grounds to take effective policy measures against acts of terror.
Keywords: New Colonialism; Violence; Terrorism; Sociology; Religion